Bisphosphonate 休薬期間が抜歯窩治癒過程に及ぼす影響についての実験的研究 - 渡邉, 竜太; 細原, 政俊; 式守, 道夫; 江㞍, 貞一; 村木, 智則; 伊藤, 友里; 笠井, 唯克; 厚地, 功誠 (日本口腔外科学会雑誌, 2014)
The use of bisphosphonate (BP) after dental extraction has been reported to cause bisphosphonate-related osteonecrosis of the jaw (BRONJ). Avoidance of oral BP is recommended; however, no guidelines exist for intravenous BP. Therefore, we evaluated the influence of intravenous BP drug holiday (BPdh) on post-extraction healing. Japanese white rabbits were used. In the sham group, saline was administered intravenously, and the mandibular premolar teeth were extracted; then, the mandible was collected 2-10 weeks after teeth extraction. In the BPdh group, zoledronate was administered intravenously. After 0, 1, 3, and 6 weeks of BPdh, the teeth were extracted. The jaws were collected 6 weeks after the tooth extractions. The healing status of the extraction socket was assessed. The cancellous bone volume (BV/ TV), trabecular separation (Tb. Sp), and trabecular number (Tb. N) of the mandibular bone lingual side were measured with microfocus X-ray images as healing index. In the sham group, bone exposure was not observed; BV/ TV 2-10 weeks after tooth extraction decreased from 54.04% to 12.30%; Tb.N decreased from 3.02/mm to 0.83/mm; Tb. Sp increased from 75.10μm to 285.31μm; and bone remodeling on cancellous bone increased at 6 weeks. The results in the sham group at post-extraction 6 weeks, serving as control, were compared with those in the BPdh group. In the BPdh group, bone was temporarily visible (BRONJ Stage 1) in the 0-3 week groups. Tb.N and BV/ TV in all of the 0-6 week groups were significantly higher than those in the control group; these values were significantly lower in the 6 week group than in the 0 week group. Tb. Sp was significantly higher in the 6 week group than in the 0 week group, but the value was significantly lower in both groups than in the control group. BP administration resulted in changes in BV/ TV, Tb. N, and Tb. Sp and a delay in the healing process at the extraction site. A possible mechanism might be as follows:(1) BP accumulates in the jaws and is incorporated into osteoclasts; (2) after apoptosis of osteoclasts, BP may reattach to the surface of new trabecular bone in the extraction wound even during BPdh. The cancellous bone in the 6-week BPdh group was closer to that in the control group than that in the 0 week BPdh group. Healing following tooth extraction in patients who receive intravenous BP therapy may be promoted by BPdh.